Determination of the strong coupling constant from the inclusive jet cross section in pp collisions at s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Royon, C.; et al. (Amer Physical Soc, 2009)
We determine the strong coupling constant alpha(s) and its energy dependence from the p(T) dependence of the inclusive jet cross section in pp collisions at s=1.96 TeV. The strong coupling constant is determined over the transverse momentum range 50 < p(T)< 145 GeV. Using perturbative QCD calculations to order O(alpha(3)(s)) combined with O(alpha(4)(s)) contributions from threshold corrections, we obtain alpha(s)(M-Z)=0.1161(-0.0048)(+0.0041). This is the most precise result obtained at a hadron-hadron collider.